UJI EFEKTIVITAS PEMBERIAN LARUTAN GULA AREN (Arenga Pinnata) TERHADAP GAMBARAN HISTOPATOLOGI HEPAR PADA TIKUS JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - Annisa Siska Afita (2020)
Hyperglycaemia causes cells to experiencing oxidative stress. This affects the long-term process of lipid and protein metabolism causes damage to liver cells. Palm sugar contains calcium and oxidative compounds useful to reduce hyperglycaemia and oxidative stress triggers. This research aimed to determine the effectiveness of palm (Arenga Pinnata) sugar solution provision on liver histopathology display of alloxan-induced male rats. This research applied pure experimental design. 30 rats were randomly put into five groups, each group totalling six rats, consisting of negative control, positive control (alloxan), and three treatment groups given alloxan and palm sugar solutions of different doses (180, 360, and 720 mg /day). It was carried out for 38 days and surgery was performed to obtain preparations and Hematoxylin-eosin staining. The blood glucose levels were measure on days 3, 17, and 31. The One Way Anova test showed significant differences between each group (p = 0.001). The Post Hoc Test showed the treatment groups had significant results compared to positive control, meaning that there was an effect of giving palm sugar solution in improving liver histopathology. The average dose of 180 mg/day was the most effective dose to improve liver histopathology and reduce blood glucose levels.